A new genus of sigmodontine rodent from Eastern Brazil and the origin of the tribe Phyllotini - Pardiñas, Ulises Francisco J. (2014)
We describe a new living genus and species of Sigmodontinae currently only known from the Brazilian National Park Sempre Vivas, Minas Gerais State. This rodent is characterized by a unique combination of traits that include, among others, a long tail, with its distal tip (approximately 2.5 to 5 cm) entirely white; skull with domed profile; long rostrum with an incipient rostral tube; and noticeable small brachyodont molars with reduced mesolophs and mesostyles present on the 1st and 2nd upper molars. Cladistic analyses of molecular (1 mitochondrial and 1 nuclear marker) and morphological characters indicate that the new genus belongs to the Phyllotini and is sister to the remainder genera of this tribe. However, contrary to other known phyllotines, the new genus shows vestigial mesolophs and mesostyles. Phyllotines are widespread in open areas, in particular desert and semideserts, mostly in the western portion of South America. The new genus described herein expands the diversity of the tribe and suggests an ancient event of diversification in eastern Brazil.